Penerapan Model Pembelajaran Cooperative Learning STADAT dengan Media Kartu Quetion Ask (Qa) Untuk Meningkatkan Hasil Belajar dan Perilaku Berkarakter Siswa - Darwito, Sugeng (Educreative : Jurnal Pendidikan Kreativitas Anak, 2020)
The application of the Student Teams Achievement Division and Tournament (STADAT) learning method is a Class Action research conducted on class VIII-I students of SMP Negeri 1 Banjar. This research was conducted in 2 cycles. The first cycle discusses the Government System in Indonesia, consisting of (1) planning, namely making learning tools (RPP-1, test questions, measuring teacher teaching and learning), (2) actions (teaching and learning teachers in class), (3) observing collaborators during teaching and learning activities. ) and (4) Reflection (discussing the strengths and weaknesses of teaching and learning activities between teachers and collaborators). Data obtained from formative tests, interview results and qualifications. The second cycle is carried out like the first cycle with material, namely Presentation of Indonesian State Sovereignty. From the research data, it is obtained that the application of STADAT cooperative learning with the Quetion Ask Card (QA) media can improve the cultural behavior and national character of grade VIII-I students. The average proportion level of increased action increased from 71.88% (satisfactory behavior) in cycle I to 85.00% (very good behavior) in cycle II. The average completeness of student learning was 59% in cycle I, increasing to 88% in cycle II.